Synthesis of Spirofluorenyl-1,2,4-oxadiazinan-5-ones through Metal-Free [3+3] Cycloaddition of N-Vinyl Fluorenone Nitrones with Aza-oxyallyl Cations - Luo, Yan; Chen, Chun-Hua; Zhang, Jin-Qi; Liang, Cui; Mo, Dong-Liang (Synthesis, 2020)
Spirofluorenyl-1,2,4-oxadiazinan-5-ones are prepared in good to excellent yields through metal-free [3+3] cycloaddition of N-vinyl fluorenone nitrones and aza-oxyallyl cations under mild reaction conditions. Detailed studies reveal that N-vinyl fluorenone nitrones show greater reactivity in [3+3] cycloadditions with aza-oxyallyl cations compared to N-alkyl/aryl fluorenone nitrones. The spirofluorenyl-1,2,4-oxadiazinan-5-ones are easily prepared on gram scale. The present method features mild reaction conditions, broad substrate scope, good functional group tolerance and efficient [3+3] cycloadditions of 9-fluorenone nitrones.
Keywords: 9-fluorenone nitrones; [3+3] cycloaddition; aza-oxyallyl cations; metal-free; spiroheterocycles